2018
DOI: 10.1186/s12879-018-3144-3
|View full text |Cite
|
Sign up to set email alerts
|

Urine IP-10 as a biomarker of therapeutic response in patients with active pulmonary tuberculosis

Abstract: BackgroundPrior to clinical trials of new TB drugs or therapeutic vaccines, it is necessary to develop monitoring tools to predict treatment outcomes in TB patients. Urine interferon gamma inducible protein 10 (IP-10) is a potential biomarker of treatment response in chronic hepatitis C virus infection and lung diseases, including tuberculosis. In this study, we assessed IP-10 levels in urine samples from patients with active TB at diagnosis, during treatment, and at completion, and compared these with levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
4
12
0
Order By: Relevance
“…CRP and IP-10 have been mostly evaluated in combination to determine if they can be used to increase the performance of differential diagnosis in TB [ 71 ]. Similar to other findings, that identified elevated concentrations of soluble IP-10 in plasma, serum or urine from PTB patients [ 72 , 73 , 74 ], this study found a declining tendency of IP-10 levels in patients that turned culture negative after anti-TB drug therapy compared to the levels at the time of initiation of treatment. Thus, the lack of treatment response could be associated with persistent high IP-10 levels.…”
Section: Discussionsupporting
confidence: 90%
“…CRP and IP-10 have been mostly evaluated in combination to determine if they can be used to increase the performance of differential diagnosis in TB [ 71 ]. Similar to other findings, that identified elevated concentrations of soluble IP-10 in plasma, serum or urine from PTB patients [ 72 , 73 , 74 ], this study found a declining tendency of IP-10 levels in patients that turned culture negative after anti-TB drug therapy compared to the levels at the time of initiation of treatment. Thus, the lack of treatment response could be associated with persistent high IP-10 levels.…”
Section: Discussionsupporting
confidence: 90%
“…These results support the research done by other groups [26][27][28][29][30], confirming the suitability of this marker for TB diagnosis. As opposed to TB diagnostic tests based on the IFNγ concentrations (IGRA), which require an incubation period with Mtb antigens, IP-10 has been shown in ours and other studies [26,[31][32][33] to be increased in serum, plasma and urine of TB patients without requiring further stimulation. Of note, in our work IFNγ was rejected for further analysis in the preliminary screening, as it did not show significant differences between groups.…”
Section: Discussionmentioning
confidence: 52%
“…IP-10 levels increase in patients with active pulmonary TB and decrease when TB treatment is complete. 19 This study aims to analyze the accuracy of the diagnosis based on the detection of the CXCL10 gene in the urine of patients with suspected pulmonary TB. The results of this study are expected to determine the accuracy of the CXCL10 gene detection method in urine as a laboratory tool for diagnosis of pulmonary TB.…”
Section: Resultsmentioning
confidence: 99%